2020
DOI: 10.21037/mhealth.2019.11.04
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic groups via video teleconferencing and the impact on group cohesion

Abstract: Background: The use of synchronous telemental health for therapy group is a relatively new area of exploration. While telegroups have demonstrated they can be helpful in providing psychoeducation, there is less known about whether synchronous remote groups can develop group cohesion and whether patients can receive the benefit of a supportive group setting.Methods: A pilot study was conducted comparing group cohesion between patients who participated in a dialectical behavior therapy (DBT) group via video tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 11 publications
5
50
2
1
Order By: Relevance
“…Overall feasibility and accessibility of group e-therapies was also found to be high ( Banbury et al, 2018 ). Whilst some participants expressed a preference to access in-person groups, this preference was outweighed by the perceived benefit of the convenience of online groups ( Lopez et al, 2020 ).…”
Section: Group E-therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall feasibility and accessibility of group e-therapies was also found to be high ( Banbury et al, 2018 ). Whilst some participants expressed a preference to access in-person groups, this preference was outweighed by the perceived benefit of the convenience of online groups ( Lopez et al, 2020 ).…”
Section: Group E-therapiesmentioning
confidence: 99%
“…Virtual group therapy creates the issue of the ‘disembodied group’, where group members cannot easily respond to cues such as the use of gaze as prompts to talk. Some studies have suggested that virtual groups are able to replicate group processes such as bonding ( Banbury et al, 2018 ), whilst other studies offering anger management and DBT found participants feel less connected ( Lopez et al, 2020 ), and exhibit lower alliance with the group facilitator than participants in face-to-face groups ( Greene et al, 2010 ). However, online groups and improved access may also lead to the strengthening of other therapeutic factors.…”
Section: Group E-therapiesmentioning
confidence: 99%
“…The group skills training component of DBT has been trialled as a standalone intervention with a range of populations and problems with promising results (Valentine et al, 2015). The facilitation of online skills groups is a relatively new endeavour and pilot studies have demonstrated that it is feasible, although participants may not feel as connected to other group members compared to face-to-face groups (Lopez et al, 2020). However, for some people the anxiety associated with attending a face-to-face group may lead to premature drop out; Whilst for others identification and loyalty to the group may assist the individual to keep attending and remaining with the programme when there are potential alliance ruptures with individual therapists .…”
mentioning
confidence: 99%
“…In this case, delivering a collaborative and meaningful team formulations session via video call was problematic. In a study comparing therapeutic groups delivered in person and via video call, it was found that while connected to the facilitator was equal in both groups, group cohesion was rated as significantly lower in the group facilitated via video (Lopez et al, 2020). The current context has shone a light on the need for reflexivity and flexibility to respond to challenges.…”
Section: Discussionmentioning
confidence: 99%